PERAN DIPLOMASI PERTAHANAN GUNA MENJAGA RUANG UDARA UNTUK KEDAULATAN NEGARA INDONESIA - Napitupulu, Heri (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The development of the strategic environment raises threats that have implications for national defense, and the South China Sea (LCS) regional dispute has become a geopolitical and geostrategic terrain in the Southeast Asian region. The United States, Australia, and the United Kingdom initiated AUKUS to counter China's aggressive activities in the Indo-Pacific. Indonesia has its own orbit with national airspace (aerial intrusion) from foreign civilian and military aircraft entering without permission is considered to violate the country's sovereign territorial boundaries. This study reveals the role of defense diplomacy to increase trust between military elements (confidence building measure) to maintain airspace through the capabilities of the defense industry. Maintaining the country's sovereignty in the airspace is the main task of the Indonesia Air Force from potential threats of traditional, non-traditional, and a combination of the two types of threats (hybrid). The principle of Indonesia's foreign policy is free-active in interpreting the meaning of the terminology of state sovereignty. The role of Defense Diplomacy to Maintain Airspace for the Sovereignty of the State of Indonesia is inseparable from three forms, namely hard power (military), soft power (diplomacy), and smart power (policy) which prioritizes mastery of science and technology.